Amphiphilic Modified Galactomannan as a Novel Potential Carrier for Hydrophobic Compounds - Cerqueira, Miguel A.; Pinheiro, Ana C.; Pastrana, Lorenzo M.; Vicente, António A. (Frontiers in Sustainable Food Systems, 2019)
The present work aims at developing and characterizing a modified galactomannan for the production of nano-sized micelles through the solvent diffusion method and its evaluation as a new carrier for hydrophobic compounds. Guar gum galactomannan was acetylated and a new polymer with different degrees of acetylation was obtained. The acetylation and substitution degree of the polymer was determined and characterized by means of Fourier transform infrared spectroscopy and thermogravimetric analysis. Galactomannan acetate (GA) was evaluated for development of micelles through the solvent diffusion method. Critical micellar concentration (CMC) was evaluated through dynamic light scattering where the effect of a wide range of GA concentrations in the micelle formation was studied. Results showed that CMC is around 0.2 mg mL−1 and an increase of GA concentration leads to the formation of monodisperse micelles with low values of polydispersity. The influence of the degree of acetylation was evaluated in terms of size average, polydispersity (PdI) and zeta potential. Transmission electron microscopy was used to evaluate micelles' morphology. It was shown that GA can be used to form micelles for the encapsulation of curcumin (used as model compound) with an encapsulation efficiency higher than 99% and a loading capacity ranging from 5.5 to 7.7%. Results showed that the degree of acetylation can be used to control particle size: micelles produced from GA with the lowest degree of acetylation have a diameter which is around 25% smaller than that of micelles produced from GA with the highest degree of acetylation. This study provides information concerning the preparation of polymeric micelles based on a modified natural galactomannan for application in the food and pharmaceutical industry. To our knowledge, it is the first work dealing with galactomannans' modification.